2017
DOI: 10.1002/cssc.201700612
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Uniform 1 cm2 Perovskite Solar Cells with an Electrochemically Deposited NiOx Hole‐Extraction Layer

Abstract: Given that the highest certified conversion efficiency of the organic-inorganic perovskite solar cell (PSC) already exceeds 22 %, which is even higher than that of the polycrystalline silicon solar cell, the significance of new scalable processes that can be utilized for preparing large-area devices and their commercialization is rapidly increasing. From this perspective, the electrodeposition method is one of the most suitable processes for preparing large-area devices because it is an already commercialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 39 publications
2
78
0
Order By: Relevance
“…The mesoporous film becomes much denser with the increasing deposition time according to the SEM images in the Supporting Information (Figure S1a–e, Supporting Information). Besides, the thickness of deposited NiO x film can be accurately controlled by adjusting the deposition time, and corresponding current density–voltage ( J – V ) characterization of PSCs has verified that the optimal ECD deposition time for fabrication of NiO x is 90 s (details can be found in Figure S1 and S2, Supporting Information), with constant current density of 0.1 mA cm −2 . The inset of Figure b illustrates the cross‐sectional image of the NiO x film prepared under optimal deposition time of 90 s and its thickness is about 40 nm, much thinner than the reported optimal thickness (50–150 nm) by solution‐derived spin‐coating method .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The mesoporous film becomes much denser with the increasing deposition time according to the SEM images in the Supporting Information (Figure S1a–e, Supporting Information). Besides, the thickness of deposited NiO x film can be accurately controlled by adjusting the deposition time, and corresponding current density–voltage ( J – V ) characterization of PSCs has verified that the optimal ECD deposition time for fabrication of NiO x is 90 s (details can be found in Figure S1 and S2, Supporting Information), with constant current density of 0.1 mA cm −2 . The inset of Figure b illustrates the cross‐sectional image of the NiO x film prepared under optimal deposition time of 90 s and its thickness is about 40 nm, much thinner than the reported optimal thickness (50–150 nm) by solution‐derived spin‐coating method .…”
Section: Resultsmentioning
confidence: 82%
“…As a result, the calculated n trap decreased from 1.76 × 10 15 cm −3 for NiO x /perovskite to 1.15 × 10 15 cm −3 for the UVO‐NiO x /perovskite, which demonstrates a reduced trap recombination at HTL/perovskite interface for the UVO‐treated NiO x . Compared to the spin‐coating method, the NiO x film fabricated by ECD method is relatively more uniform and is more scalable for large area devices with absence of mechanical fabrication procedure . Moreover, the devices have all presented good uniformity without edge influence (Figure c), where J–V characteristics have been measured at different positions.…”
Section: Resultsmentioning
confidence: 99%
“…That is slightly lower than mesoporous‐containing perovskites . Planar PSCs do not reach world records yet; researchers are less willing to switch from meso to planar, even though it is industrially more preferable …”
Section: Structural Influence On the Stability Of Pscsmentioning
confidence: 99%
“…Seongrok et al used NiO x based HTL in their inverted perovskite architecture which exhibited an efficiency of 16.4% [53]. Park et al also fabricated NiO x as HTL layer by electrochemical method and reported a power conversion efficiency of 17% for 1 cm 2 area devices [54]. Furthermore, many groups have suggested doping of a transition metal in NiO x to enhance the electrical properties and morphology of the layer.…”
Section: Reduction In Non-radiative Lossesmentioning
confidence: 99%